Mapping the intellectual public sphere in China today. (March 2018) - Cheek, Timothy; Ownby, David; Fogel, Joshua
The papers in this research dialogue section are the product of a project that examines intellectual life in China since the 1990s – chiefly the efforts by academic public intellectuals to rethink China's past, present, and future in light of the excesses of Mao's revolution, the challenges emerging from reform, and the rise of China to the status of world economic power. Chinese scholars, having benefited from China's openness to the world and the relative relaxation of political pressure in China (until recently), have much to say about China and the world that merits our attention. Through creative collaboration between Chinese and international scholars, the articles collected here explore that intellectual public sphere since the late 1990s. The articles were written in Chinese by young PRC scholars and rendered into English through 'collaborative translation' teams that pair these Chinese with non-Chinese scholars based in Canadian universities. The net result, grounded on repeated conversations and revisions, is not a simple translation but a co-production of knowledge about China that aims to capture the discourse of Chinese scholarship in a way to make it meaningful to anglophone readers. The articles themselves are not traditional surveys of academic scholarship. Rather they map significant areas of an intellectual world and the arguments within it. Three widely accepted intellectual streams of thought ( sichao 思潮) organize these soundings: liberals, New Left, and New Confucian. These reports explore connections between and diversity within and beyond each.